O emprego de um sensor ultrassônico para medidas de posição versus tempo de um sistema massa-mola - Carvalho, Roberta Vieira (2017)
Many topics of science and technology are becoming more popular nowadays. For this reason the education of young students in a high school should involve innovative methods of learning on a regular basis. In this context, we developed a set of theoretical and experimental classroom activities to study the simple harmonic motion (SHM). The activity set consists of oral explanations, assignments, slide presentations, apps that simulate the SHM, and an experimental kit to measure the position versus time of a mass coupled to a spring. This measurement is performed using an HC-SR04 ultrasonic sensor that is interfaced to a computer through an Arduino board. The Python language is used to plot a curve, a sinusoidal function that describes the object's motion, over the experimental data. These activities were applied to students of the Colégio Estadual Ariston Gomes da Silva, a secondary school in Iporá-GO, Brazil. The methodology of learning was based on the Ausubel's learning theory, in which the progressive differentiation and reconciliation integrative were considered. After the application of the activities, we apply a survey to perform a diagnostic evaluation. We verify that the students really could understand some important concepts for SHM.